SETOUCHI HIGH-MG ANDESITES REVISITED: GEOCHEMICAL EVIDENCE FOR MELTING OF SUBDUCTING SEDIMENTS - Shimoda G.; Ishizaka K.; Tatsumi Y.; Nohda S.; Jahn B.M. (My University, 1998)
In order to evaluate the mechanism of production of unusual high-Mg andesite (HMA) magmas, Pb–Nd–Sr isotopic compositions were determined for HMAs and basalts from the Miocene Setouchi volcanic belt in the SW Japan arc. The isotopic compositions of Setouchi rocks form mixing lines between local oceanic sediments and Japan Sea backarc basin basalts, suggesting a significant contribution of the subducting sediment component to the HMA magma generation. Mixing calculations using compositions of an inferred original mantle and local oceanic sediments suggest that a sediment-derived melt, neither an H2O-rich fluid nor an amphibolite/eclogite-derived melt, could have been produced first and served as a plausible metasomatic agent for the HMA magma source. The unusual tectonic setting, including subduction of a newly-borne hence hot plate, may be responsible for melting of subducting sediments.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен